The Chinese-German Journal of Clinical Oncology - Ho, Anthony D.; Chen, Anmin; Yu, Shiying; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The Chinese-German Journal of Clinical Oncology is an international professional academic periodical on oncology, being co-edited by China and Germany. The Journal, with the authors from around world, especially from China, is dominated in introducing the clinical experience of diagnosis and treatment as well as leading scientific research archievement in the tumor domain, in addition to report basic theory researches which help instruct the clinical practice of oncology and closely connect with the discipline. All the manuscripts are published in English. .
Keywords: Cancer research; Oncology; Surgical oncology; Oncology; Surgical Oncology; Cancer Research